Applied Adhesive Bonding in Science and Technology - Özer, Halil (IntechOpen, 2018)
This book brings together scientists and provides the reader with a comprehensive overview of some recent developments in the field of adhesive bonding with the contributions of internationally recognized authors. This book is divided into three sections: "Structural Adhesive Bonding," "Wood Adhesive Bonding," and "Adhesive Bonding in Medical Applications." Each section presents an important review and some applications of the adhesive bonding in various different disciplines. I hope that the book published in open access will help researchers to benefit from it.